Tendências no ensino da matemática no Brasil: uma análise a partir de livros didáticos - Alberti, Luana Angélica (2016)
This dissertation summarizes the research that aimed to identify and analyze how trends in Mathematics Education, which were suggested by the National Curriculum Standards, are dealt in mathematics textbooks that were developed after implantation of primary school with duration of nine years in Brazil. Initally, the role, importance and how was the inclusion of the textbook in Brazilian schools are identified in the research. In a second moment the research is set in the field of mathematics education, specifically regarding to the teaching of Mathematics and its changes over time, having as the main point, the presentation of trends in mathematics education. The research was performed through examination of the didactic collection, dedicated to the final years of primary school, with the highest number of copies distributed by the Programa Nacional do Livro Didático (PNLD), 2014 edition. The development of this study was made in accordance with the assumptions of qualitative research, guided by the methodological procedures of content analysis. Starting from the assumed conceptions, it was verified the presence of one hundred fifty-eight situations involving tendencies in Mathematics Education, which converged to some key trends. The identified trends were History of Mathematics, Mathematics and technology, Games and didactic materials, Ethnomatematics, Interdisciplinarity, Pedagogy of projects, Resolution of Problems and, especially, Contextualization, distributed among the various sections that constitute the chapters of the textbooks of the collection. Finally, it can be seen that the trends are presented as historical approach to presentation and / or development of mathematical content, in mathematical situations as a context for the development of mathematical content and through investigative situations as a mathematics learning scenario, which are the three categories discussed in this dissertation.